IMPLEMENTASI PASAL 3 UNDANG-UNDANG NOMOR 5 TAHUN 1960 TENTANG PERATURAN DASAR POKOK-POKOK AGRARIA TERHADAP HAK ULAYAT ATAS TANAH DI DESA ADAT YEH SANIH - Putri, Made Kharisma; Dantes, Komang Febrinayanti; Adnyani, Ni ketut sari (Universitas Pendidikan Ganesha, 2024)
This research generally to reveal related problems contained in Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles, Especially examining the provisions of Article 3 of the UUPA on customary rights to Pelaba pura land in Yeh Sanih Traditional Village and analyzing legal certainty and efforts of the Yeh Sanih Traditional Village community in maintaining customary rights to Pelaba pura land in Yeh Sanih Traditional Village. To facilitate this research, the method used is empirical legal research with the nature of the research, namely descriptive. The research location was conducted in Yeh Sanih Traditional Village using data collection techniques through observation, interviews, document studies. Determination of the sample of this research using purposive sampling so that the sample can represent the research objectives and prevent the exit from the topic od discussion and the results obtained are relevant and accurate. The result of the study were processed using qualitative analysis. With the help of this research method, the results obtained are the respect for customary rights has been regulated in Article 3 of the UUPA along with the state constitution. With the existence of Pelaba pura land located in the territory of the Yeh Sanih customary village, it proves that the Yeh Sanih Customary Village has the right of the land based on Bali Provincial Regulation Number 4 of 2019 concering Customary Villages and even though it does not yet have a certificate but there is already evidence of ownership for generations. To ensure legal certainty of pelaba pura land, land registration is needed. Pelaba pura land registration will be included in customary land registration in village asset. Suggestions can be given to provide more information regerding the importance of land registration, especially on village assets so that villages can collect land data on village assets that do not yet have certificates so that rights to the land can be protected,